SUCCESS OF STORYTELLING IN BRAND BUILDING: LOOKING THROUGH THE LENS OF NEUROSCIENCE - Chakraborty, Tanusree (International Journal of Psychosocial Rehabilitation, 2020)
Neuroscience has grown in bounds in the recent decade, but it is yet to spread fast into the realm of marketing mainly because of dearth of trained researchers in cognitive neuroscience. Understanding the cognitive processes of the human brain will allow the business to obtain accurate information about customers’ decision- making process, which will help organizations to formulate STP and to develop various marketing engagement strategies for long-term sustainability of a business. In neuro marketing, customer experience allows the marketer to connect with customers innovatively beyond tangible touch points, beyond brick mortar stores, through smartphones or through tablet apps. The general understanding or overview of consumer decision-making process is not possible to get via conventional marketing research methods (e.g., interviews, questionnaires, focus groups).This thought is mainly supported by the logic that consumer or customer cannot (or do not want to) fully explain their liking and disliking process when explicitly asked (Calvert & Brammer, 2012).